Copolymer, piezoelectric material, piezoelectric film, and piezoelectric element
By using a copolymer containing an oxazolidinone skeleton and a 2-fluoroacrylonitrile structural unit, the problem of insufficient heat resistance of existing ferroelectric polymer piezoelectric materials is solved, and high heat resistance and piezoelectric characteristics are achieved Piezoelectric film and piezoelectric components with a widen use temperature range.
Patent Information
- Application Number
- CN202380051709.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-20
- Filing Date
- 2023-06-02
- Publication Date
- 2025-02-18
AI Technical Summary
The heat resistance of existing ferroelectric polymer piezoelectric materials is insufficient, resulting in loss of physical properties such as piezoelectric properties and elastic modulus at high temperatures, and the use temperature range is narrow.
Using a copolymer containing an oxazolidinone skeleton and structural units from 2-fluoroacrylonitrile, the intermolecular interaction is enhanced through the formation of intermolecular hydrogen bonds, inhibiting the cancellation of dipole moments of nitrile groups, thereby improving heat resistance and pressure Electrical characteristics.
It realizes a piezoelectric film with high heat resistance and piezoelectric characteristics, expands the temperature range of piezoelectric components, and has excellent heat resistance and piezoelectric properties.
Smart Images

Figure CN119487089A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a copolymer, a piezoelectric material, a piezoelectric film and a piezoelectric element.
[0002] This application claims priority based on Japanese Patent Application No. 2022-115444 filed in Japan on July 20, 2022, the contents of which are cited herein. Background Art
[0003] PZT (PbZrO3-PbTiO3 solid solution) is a ceramic material that has been used as the piezoelectric material of the piezoelectric element. However, PZT has the defect of being very brittle because it is a ceramic containing lead. Therefore, as a piezoelectric material, a material with low environmental burden and high flexibility is sought.
[0004] As a piezoelectric material that meets such requirements, it is considered to use a polymer piezoelectric material. As a polymer piezoelectric material, there are ferroelectric polymers such as polyvinylidene fluoride (PVDF), vinylidene fluoride-trifluoroethylene copolymer (P(VDF-TrFE)). However, the heat resistance of these ferroelectric polymers is insufficient. Therefore, if the piezoelectric body composed of existing ferroelectric polymers is raised to a high temperature, it will lose its piezoelectric properties, and physical properties such as elastic modulus will also deteriorate. Therefore, the temperature range in which the piezoelectric element having a piezoelectric body composed of existing ferroelectric polymers can be used is narrow.
[0005] In addition, as a piezoelectric material, there is an amorphous polymer piezoelectric material, which obtains piezoelectricity by being polarized at a temperature near the glass transition temperature and then cooled. If the amorphous polymer reaches a temperature near the glass transition temperature, the piezoelectric property disappears. Therefore, an amorphous polymer piezoelectric material with a high glass transition temperature and good heat resistance is sought.
[0006] As the amorphous polymer piezoelectric material with high glass transition temperature, vinylidene cyanide-vinyl acetate copolymer (for example, with reference to patent documentation 1) can be cited. However, vinylidene cyanide-vinyl acetate copolymer needs to use vinylidene cyanide which is difficult to operate as raw material monomer. Specifically, vinylidene cyanide is easily homopolymerized due to the trace moisture in the atmosphere. Therefore, the deviation when using vinylidene cyanide as the polymer manufacturing of raw material monomer is large, and it is difficult to be used as amorphous polymer piezoelectric material.
[0007] In addition, as a raw material monomer having a nitrile group like vinylidene cyanide, a polymer using 2-fluoroacrylonitrile is known (for example, refer to Non-Patent Document 1). 2-fluoroacrylonitrile has good stability. However, the existing polymer using 2-fluoroacrylonitrile as a raw material monomer has a low glass transition point and insufficient heat resistance.
[0008] Prior art literature
[0009] Patent Literature
[0010] Patent Document 1: International Publication No. 1991 / 013922
[0011] Non-patent literature
[0012] Non-patent document 1: Journal of the Chemical Society of Japan, 1985, (10), P.1862-1868 Summary of the invention
[0013] Technical problem to be solved by the invention
[0014] Currently, there is a need for a polymer piezoelectric material that can produce a piezoelectric film having high heat resistance and piezoelectric characteristics.
[0015] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide a copolymer that can be used as a piezoelectric material capable of obtaining a piezoelectric film having high heat resistance and piezoelectric characteristics.
[0016] Another object of the present invention is to provide a piezoelectric material comprising the copolymer of the present invention and capable of obtaining a piezoelectric film having high heat resistance and piezoelectric characteristics.
[0017] Another object of the present invention is to provide a piezoelectric film having high heat resistance and piezoelectric characteristics, which includes the copolymer of the present invention, and a piezoelectric element having high heat resistance and piezoelectric characteristics, which includes the piezoelectric film of the present invention.
[0018] Technical solutions for solving technical problems
[0019] In order to solve the above-mentioned problems, the following technical solutions are provided.
[0020] The copolymer according to one embodiment of the present invention has a structural unit represented by the following general formula (1) and a structural unit represented by the following formula (2).
[0021]
[0022] (In general formula (1), R 1 is any one selected from the group consisting of a hydrogen atom, a methyl group, a dimethyl group, an ethyl group, an isopropyl group, an isobutyl group, a phenyl group, and a benzyl group, and R 2 is a hydrogen atom or a methyl group, or R 1 and R 2 Together with the oxazolidinone ring, it forms a benzoxazolidinone skeleton.)
[0023] Effects of the Invention
[0024] The copolymer of the present invention has a structural unit represented by the general formula (1) and a structural unit represented by the formula (2). Therefore, the copolymer of the present invention can be used as a piezoelectric material capable of obtaining a piezoelectric film having high heat resistance and piezoelectric characteristics.
[0025] Furthermore, since the piezoelectric material of the present invention includes the copolymer of the present invention, a piezoelectric film having high heat resistance and piezoelectric characteristics can be obtained.
[0026] Furthermore, the piezoelectric film of the present invention includes the copolymer of the present invention. Therefore, the piezoelectric film of the present invention and the piezoelectric element of the present invention having the piezoelectric film of the present invention are excellent in heat resistance and piezoelectric characteristics. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 Example 3 1 H-NMR measurement chart.
[0028] Figure 2 Example 3 19 F-NMR measurement chart.
[0029] Figure 3 Example 8 1 H-NMR measurement chart.
[0030] Figure 4 Example 8 19 F-NMR measurement chart. DETAILED DESCRIPTION
[0031] In order to solve the above-mentioned problems, the present inventors have focused on polymers using a stable monomer having a nitrile group (—C≡N) as a raw material monomer and have conducted intensive studies.
[0032] The results show that the copolymer having a structural unit containing an oxazolidinone skeleton and a structural unit derived from acrylonitrile forms a piezoelectric material capable of obtaining a piezoelectric film having good heat resistance and piezoelectric properties. It is speculated that the reason for this is that in the above-mentioned copolymer, by including a structural unit of an oxazolidinone skeleton having high polarity, the ordered structure that can be formed by the polar group derived from acrylonitrile, i.e., the nitrile group, is disrupted, and the nitrile group is difficult to be oriented in a manner that cancels out the polarity of each other.
[0033] Therefore, the present inventors have focused on the dipole moment of a copolymer having a structural unit containing an oxazolidinone skeleton and a structural unit derived from acrylonitrile, and have repeatedly studied to further improve the piezoelectric properties in a piezoelectric film containing the above-mentioned copolymer. However, in a piezoelectric film containing the copolymer, it is difficult to improve the piezoelectric properties for the reasons shown below.
[0034] That is, in order to improve the piezoelectric properties of the piezoelectric film comprising the above-mentioned copolymer, it is desirable to avoid the nitrile groups contained in the structural units from acrylonitrile in the above-mentioned copolymer from being oriented in a manner that the dipole moments are offset from each other. However, in the polymer using acrylonitrile as the raw monomer, the symmetry of the dipole moment relative to the polymer main chain direction is low. In addition, even if the compound formed by bonding vinyl groups on the nitrogen atoms of acrylonitrile and oxazolidone skeletons is copolymerized, the offset of the dipole moments of the nitrile groups from acrylonitrile cannot be fully suppressed. Therefore, in the piezoelectric film comprising the above-mentioned copolymer, it is difficult to further improve the piezoelectric properties.
[0035] Therefore, the present inventors have repeatedly studied the use of a stable monomer having a nitrile group, which is a raw material monomer capable of obtaining a polymer having a high symmetry of dipole moment with respect to the polymer main chain direction, in place of acrylonitrile polymer.
[0036] As a result, the inventors found that it is sufficient to prepare a copolymer having a specific structural unit containing an oxazolidinone skeleton and a structural unit derived from 2-fluoroacrylonitrile.
[0037] That is, in the copolymer having a specific structural unit containing an oxazolidinone skeleton and a structural unit derived from 2-fluoroacrylonitrile, the fluorine group contained in the structural unit derived from 2-fluoroacrylonitrile forms an intermolecular hydrogen bond, so that the interaction between the molecules becomes stronger. As a result, it is estimated that the heat resistance of the piezoelectric film using the copolymer becomes better than the case where a copolymer having a structural unit derived from acrylonitrile instead of a structural unit derived from 2-fluoroacrylonitrile is used.
[0038] In addition, the copolymer has a nitrile group and a fluorine group contained in the structural unit derived from 2-fluoroacrylonitrile, and therefore, the symmetry of the dipole moment relative to the polymer main chain direction is high. Therefore, the copolymer suppresses the mutual cancellation of the dipole moments, thereby being able to show a high polarity. It is thus inferred that the piezoelectric film using the copolymer obtains better piezoelectric properties than the case where a copolymer having a structural unit derived from acrylonitrile is used instead of a structural unit derived from 2-fluoroacrylonitrile.
[0039] Furthermore, the present inventors produced a copolymer (polymer) having a specific structural unit including an oxazolidinone skeleton and a structural unit derived from 2-fluoroacrylonitrile, and confirmed that the copolymer had good heat resistance and that a piezoelectric film using the copolymer as a piezoelectric material had good piezoelectric properties, thereby arriving at the present invention.
[0040] In addition, the present inventors have explored the use of compounds in which the fluoro group (-F) possessed by 2-fluoroacrylonitrile is other halo groups (chloro group (-Cl), bromo group (-Br), iodo group (-I)) to replace 2-fluoroacrylonitrile as a raw material monomer. However, compounds in which the fluoro group possessed by 2-fluoroacrylonitrile is other halo groups are difficult to copolymerize with compounds in which vinyl groups are bonded to the nitrogen atom of the oxazolidinone skeleton. Therefore, it is impossible to use compounds in which the fluoro group possessed by 2-fluoroacrylonitrile is other halo groups to replace 2-fluoroacrylonitrile as a raw material monomer to manufacture a copolymer with a compound in which vinyl groups are bonded to the nitrogen atom of the oxazolidinone skeleton.
[0041] The present invention includes the following aspects.
[0042] [1] A copolymer comprising a structural unit represented by the following general formula (1) and a structural unit represented by the following formula (2).
[0043]
[0044] (In general formula (1), R 1 is any one selected from the group consisting of a hydrogen atom, a methyl group, a dimethyl group, an ethyl group, an isopropyl group, an isobutyl group, a phenyl group, and a benzyl group, and R 2 is a hydrogen atom or a methyl group, or R 1 and R 2 Together with the oxazolidinone ring, it forms a benzoxazolidinone skeleton.)
[0045] [2] The copolymer according to [1], wherein in the general formula (1), R 1 is a hydrogen atom, R 2 A hydrogen atom or a methyl group.
[0046] [3] The copolymer according to [1] or [2], wherein the content of the structural unit represented by the formula (2) is 10 to 80 mol%.
[0047] [4] A piezoelectric material comprising the copolymer according to any one of [1] to [3].
[0048] [5] A piezoelectric film comprising the copolymer according to any one of [1] to [3].
[0049] [6] A piezoelectric element comprising the piezoelectric film according to [5] and electrodes disposed on one surface and the other surface of the piezoelectric film, respectively.
[0050] Hereinafter, the copolymer, piezoelectric material, piezoelectric film, and piezoelectric element of the present invention will be described in detail.
[0051] [Copolymer]
[0052] The copolymer (polymer) of the present embodiment has a structural unit represented by the general formula (1) and a structural unit represented by the formula (2).
[0053] In the structural unit represented by the formula (1) possessed by the copolymer of the present embodiment, R 1 is any one selected from the group consisting of a hydrogen atom, a methyl group, a dimethyl group, an ethyl group, an isopropyl group, an isobutyl group, a phenyl group, and a benzyl group, and R 2 is a hydrogen atom or a methyl group. 1 and R 2 The copolymer of the present embodiment can be easily produced because it is the above-mentioned group. 1 and R 2 Since R of the structural unit represented by formula (1) is 1 and R 2 It has no polarity, so it is preferred that the volume is small. This is because the volume ratio of the polar part in the whole copolymer is relatively increased, which is beneficial to improve the piezoelectric properties of the piezoelectric film using it. Specifically, it is preferred that R 1 is a hydrogen atom, R 2 Further, as can be seen from the examples, in order to be used as a material for a piezoelectric film having good heat resistance and piezoelectric properties, R 1 is a hydrogen atom, R 2 It is methyl.
[0054] In the structural unit represented by formula (1), R 1 and R 2 It may also form a benzoxazolidinone skeleton together with the oxazolidinone ring. 1 and R 2 When a benzoxazolidinone skeleton is formed together with an oxazolidinone ring, it can be easily produced and can be used as a material for a piezoelectric film having excellent heat resistance and piezoelectric characteristics.
[0055] In the copolymer of the present embodiment, the arrangement order of the structural unit represented by formula (1) as a repeating unit and the structural unit represented by formula (2) is not particularly limited. In addition, in the copolymer of the present embodiment, the number of structural units represented by formula (1) and the number of structural units represented by formula (2) may be the same or different. Therefore, the copolymer of the present embodiment may be an alternating arrangement portion in which the structural units represented by formula (1) and the structural units represented by formula (2) are alternately arranged, a random arrangement portion in which the structural units represented by formula (1) and the structural units represented by formula (2) are arranged in a disordered manner, and a block arrangement portion having a continuous arrangement portion of the structural units represented by formula (1) and the structural units represented by formula (2) are continuously arranged The polymer is distributed in an arbitrary proportion. In the copolymer of the present embodiment, in order to make it difficult for the fluorine group and the nitrile group contained in the structural unit represented by formula (2) to be oriented in a manner that offsets each other's polarity, and to be used as a piezoelectric material with good heat resistance and piezoelectric properties, it is preferably included in the alternating arrangement portion.
[0056] In the copolymer of the present embodiment, the content of the structural unit represented by formula (1) is preferably 10 to 80 mol%, more preferably 20 to 70 mol%, and further preferably 30 to 60 mol%. When the content of the structural unit represented by formula (1) is 10 mol% or more, the copolymer has further better heat resistance. In addition, when the content of the structural unit represented by formula (1) is 80 mol% or less, the piezoelectric film containing the copolymer can be prevented from becoming hard and brittle due to excessive content of the structural unit represented by formula (1). In addition, when the content of the structural unit represented by formula (1) is 80 mol% or less, the insulation resistance of the copolymer caused by moisture absorption of the structural unit represented by formula (1) can be suppressed.
[0057] In the copolymer of the present embodiment, the content of the structural unit represented by formula (2) is preferably 10 to 80 mol%, more preferably 20 to 70 mol%, and further preferably 30 to 60 mol%. When the content of the structural unit represented by formula (2) is 10 mol% or more, it becomes a copolymer having high insulation resistance and capable of forming a soft piezoelectric film. In addition, when the content of the structural unit represented by formula (2) is 80 mol% or less, it is easy to ensure the content of the structural unit represented by formula (1). As a result, the fluorine group and nitrile group contained in the structural unit represented by formula (2) are difficult to be oriented in a manner that cancels out the polarity of each other, and a copolymer of a piezoelectric film having better heat resistance and piezoelectric properties can be formed.
[0058] The copolymer of this embodiment may also contain one or more structural units other than the structural unit represented by formula (1) and the structural unit represented by formula (2) as required. As other structural units, for example, known monomers having polymerizable unsaturated bonds such as acrylonitrile or structural units derived from oligomers can be cited.
[0059] Among the structural units contained in the copolymer of this embodiment, the total content of the structural units represented by formula (1) and the structural units represented by formula (2) is preferably 50% by mass or more, more preferably 80% by mass or more, and may be 90% by mass or more, or may be only the structural units represented by formula (1) and the structural units represented by formula (2).
[0060] The weight average molecular weight (Mw) of the copolymer of the present embodiment is preferably 10,000 to 1,000,000. When the weight average molecular weight (Mw) of the copolymer is 10,000 or more, the film-forming property becomes good, and the piezoelectric film including the copolymer of the present embodiment can be easily manufactured. When the weight average molecular weight (Mw) of the copolymer is 1,000,000 or less, it can be easily dissolved in a solvent, and a piezoelectric film can be easily manufactured using a coating liquid dissolved in a solvent.
[0061] "Method for producing copolymer"
[0062] The copolymer of the present embodiment can be produced, for example, by radical copolymerization using a raw material monomer containing a compound as a source of the structural unit represented by formula (1) and 2-fluoroacrylonitrile and a polymerization initiator such as azobisbutyronitrile according to a known method.
[0063] The polymerization conditions such as reaction temperature and reaction time when producing the copolymer of the present embodiment can be appropriately determined according to the composition of the raw material monomers and the like.
[0064] The compound from which the structural unit represented by formula (1) is derived is a compound having an oxazolidinone skeleton and atoms bonded to carbon atoms of the oxazolidinone skeleton identical to those of the structural unit represented by formula (1), and a vinyl group bonded to a nitrogen atom of the oxazolidinone skeleton.
[0065] The compound as the source of the structural unit represented by formula (1) specifically includes: N-vinyl-oxazolidinone, N-vinyl-5-methyloxazolidinone, N-vinyl-4-methyloxazolidinone, N-vinyl-4,4-dimethyloxazolidinone, N-vinyl-4-ethyloxazolidinone, N-vinyl-4-propyloxazolidinone, N-vinyl-4-isopropyloxazolidinone, N-vinyl-4-isobutyloxazolidinone, N-vinyl-4-phenyloxazolidinone, N-vinyl-4-benzyloxazolidinone, N-vinyl-2-benzoxazolinone, etc., which can be appropriately determined according to the structure of the copolymer of this embodiment as the target.
[0066] "Piezoelectric Materials"
[0067] The piezoelectric material of the present embodiment includes the copolymer of the present embodiment. The copolymer of the present embodiment contained in the piezoelectric material of the present embodiment may be only one, or may be more than two. In addition, the piezoelectric material of the present embodiment may include one or more known polymers other than the copolymer of the present embodiment together with the copolymer of the present embodiment as needed.
[0068] "Piezoelectric film"
[0069] The piezoelectric film of this embodiment includes the copolymer of this embodiment.
[0070] The piezoelectric film of the present embodiment can be manufactured by, for example, the method shown below. The piezoelectric material of the present embodiment, which includes the copolymer of the present embodiment, is dissolved in a known solvent such as N,N-dimethylformamide to prepare a coating liquid. Then, the coating liquid is applied to a peelable substrate in a specified thickness to form a coating film. As the substrate, a known substrate such as a substrate composed of a resin film such as polyethylene terephthalate (PET) can be used. The coating method of the coating liquid can use a known method according to the coating thickness, the viscosity of the coating liquid, and the like. Then, the coating film is dried to remove the solvent in the coating film to obtain a piezoelectric material sheet.
[0071] Then, the piezoelectric material sheet is peeled off from the substrate, and electrodes made of a known conductive material such as aluminum are respectively provided on one surface and the other surface of the piezoelectric material sheet, and a voltage is applied at a temperature near the glass transition temperature of the piezoelectric material forming the piezoelectric material sheet, and then cooled while the voltage is applied. Thus, piezoelectricity is obtained. Through the above steps, a sheet-shaped piezoelectric film is obtained.
[0072] The electrodes for obtaining piezoelectricity may be directly used as a member for forming a piezoelectric element, or may be removed.
[0073] "Piezoelectric element"
[0074] The piezoelectric element of this embodiment has the piezoelectric film of this embodiment and an electrode disposed on the surface of the piezoelectric film. Specifically, a piezoelectric element having a sheet-shaped piezoelectric film and electrodes disposed on one surface and the other surface of the piezoelectric film can be cited. As the material of the electrode, a known conductive material such as aluminum can be used.
[0075] The piezoelectric element of the present embodiment can be manufactured by, for example, providing electrodes on one surface and the other surface of a piezoelectric film by a known method such as a vapor deposition method.
[0076] The copolymer of this embodiment has a structural unit represented by general formula (1) and a structural unit represented by formula (2). Therefore, the copolymer of this embodiment can be used as a piezoelectric material capable of obtaining a piezoelectric film having high heat resistance and piezoelectric characteristics.
[0077] Furthermore, since the piezoelectric material of the present embodiment includes the copolymer of the present embodiment, a piezoelectric film having high heat resistance and piezoelectric characteristics can be obtained.
[0078] In addition, the piezoelectric film of the present embodiment includes the copolymer of the present embodiment. Therefore, the piezoelectric film of the present embodiment and the piezoelectric element of the present embodiment including the piezoelectric film of the present embodiment are excellent in heat resistance and piezoelectric characteristics.
[0079] Although the embodiments of the present invention have been described in detail above, each configuration in each embodiment and its combination are merely examples, and addition, omission, substitution, and other changes of the configuration may be made without departing from the gist of the present invention.
[0080] Example
[0081] "Example 1"
[0082] In a 100 ml Schlenk tube, 0.6 ml (4 mmol) of N-vinyl-oxazolidinone represented by the following general formula (11) and 0.9 ml (12 mmol) of 2-fluoroacrylonitrile were mixed, 12.4 mg (0.08 mmol) of azobisisobutyronitrile was added, and the mixture was reacted at 60° C. for 2 hours. The reaction product was added to 200 ml of methanol, reprecipitated, filtered and dried, thereby obtaining 0.6 g of the polymer of Example 1. The yield was 40%.
[0083]
[0084] (In general formula (11), R 2 is a hydrogen atom.)
[0085] The polymer of Example 1 was subjected to nuclear magnetic resonance (NMR) analysis using a NMR device (trade name: JNM-ECA500, manufactured by JEOL Ltd.) and dimethyl sulfoxide d6 (DMSO-d6) as a solvent.1 H-NMR determination and 19 F-NMR measurement to determine the molecular structure.
[0086] As a result, it was confirmed that the polymer of Example 1 had a structural unit represented by the general formula (1) (R 1 and R 2 is a hydrogen atom. ) and a copolymer of a structural unit represented by formula (2).
[0087] In addition, according to Example 1 1 H-NMR spectrum and 19 The composition ratio was calculated from the integrated value of each signal in the F-NMR spectrum. As a result, the content of the structural unit represented by the formula (2) contained in the polymer of Example 1 was 76%.
[0088] "Example 2"
[0089] In a 100 ml Schlenk tube, 0.9 ml (4 mmol) of N-vinyl-oxazolidinone and 0.4 ml (6 mmol) of 2-fluoroacrylonitrile were mixed, and 7.8 mg (0.05 mmol) of azobisisobutyronitrile was added, and the mixture was reacted at 60° C. for 2 hours. The reaction product was added to 200 ml of methanol, reprecipitated, filtered and dried, thereby obtaining 0.7 g of the polymer of Example 2. The yield was 62%.
[0090] The polymer of Example 2 was subjected to the same treatment as that of the polymer of Example 1. 1 H-NMR determination and 19 The molecular structure was determined by F-NMR measurement. The results confirmed that, like the polymer of Example 1, the polymer of Example 2 has a structural unit represented by the general formula (1) (R in the general formula (1) 1 and R 2 is a hydrogen atom. ) and a copolymer of a structural unit represented by formula (2).
[0091] In addition, according to Example 2 1 H-NMR spectrum and 19 The composition ratio was calculated from the integrated value of each signal in the F-NMR spectrum. As a result, the content of the structural unit represented by the formula (2) contained in the polymer of Example 2 was 59%.
[0092] "Example 3"
[0093] In a 100 ml Schlenk tube, 0.6 ml (6 mmol) of N-vinyl-oxazolidinone and 0.4 ml (6 mmol) of 2-fluoroacrylonitrile were mixed, 9.1 mg (0.06 mmol) of azobisisobutyronitrile was added, and the mixture was reacted at 60° C. for 2 hours. The reaction product was added to 200 ml of methanol, reprecipitated, filtered and dried, thereby obtaining 0.5 g of the polymer of Example 3. The yield was 48%.
[0094] The polymer of Example 3 was subjected to the same treatment as that of the polymer of Example 1. 1 H-NMR determination and 19 F-NMR measurement to determine the molecular structure. Figure 1 Example 1 1 H-NMR measurement chart. Figure 2 Example 3 19 F-NMR measurement chart.
[0095] As a result, it was confirmed that, similar to the polymer of Example 1, the polymer of Example 3 had a structural unit represented by the general formula (1) (R 1 and R 2 is a hydrogen atom. ) and a copolymer of a structural unit represented by formula (2).
[0096] In addition, according to Example 3 1 H-NMR spectrum and 19 The composition ratio was calculated from the integrated value of each signal in the F-NMR spectrum. As a result, the content of the structural unit represented by the formula (2) contained in the polymer of Example 3 was 50%.
[0097] "Example 4"
[0098] In a 100 ml Schlenk tube, 0.6 ml (6 mmol) of N-vinyl-oxazolidinone and 0.3 ml (4 mmol) of 2-fluoroacrylonitrile were mixed, and 7.9 mg (0.05 mmol) of azobisisobutyronitrile was added, and the mixture was reacted at 60° C. for 2 hours. The reaction product was added to 200 ml of methanol, reprecipitated, filtered and dried, thereby obtaining 0.6 g of the polymer of Example 4. The yield was 58%.
[0099] The polymer of Example 4 was subjected to the same treatment as that of the polymer of Example 1. 1 H-NMR determination and 19 The molecular structure was determined by F-NMR measurement. The results confirmed that, like the polymer of Example 1, the polymer of Example 4 has a structural unit represented by the general formula (1) (R in the general formula (1) 1 and R 2 is a hydrogen atom. ) and a copolymer of a structural unit represented by formula (2).
[0100] In addition, according to Example 4 1 H-NMR spectrum and 19 The composition ratio was calculated from the integrated value of each signal in the F-NMR spectrum. As a result, the content of the structural unit represented by the formula (2) contained in the polymer of Example 4 was 41%.
[0101] "Example 5"
[0102] In a 100 ml Schlenk tube, 0.6 ml (12 mmol) of N-vinyl-oxazolidinone and 0.4 ml (6 mmol) of 2-fluoroacrylonitrile were mixed, 9 mg (0.05 mmol) of azobisisobutyronitrile was added, and the mixture was reacted at 60° C. for 2 hours. The reaction product was added to 200 ml of methanol, reprecipitated, filtered and dried, thereby obtaining 0.7 g of the polymer of Example 5. The yield was 59%.
[0103] The polymer of Example 5 was subjected to the same treatment as that of the polymer of Example 1. 1 H-NMR determination and 19 The molecular structure was determined by F-NMR measurement. The results confirmed that, like the polymer of Example 1, the polymer of Example 5 has a structural unit represented by the general formula (1) (R in the general formula (1) 1 and R 2 is a hydrogen atom. ) and a copolymer of a structural unit represented by formula (2).
[0104] In addition, according to Example 5 1 H-NMR spectrum and 19 The composition ratio was calculated from the integrated value of each signal in the F-NMR spectrum. As a result, the content of the structural unit represented by the formula (2) contained in the polymer of Example 5 was 25%.
[0105] "Example 6"
[0106] In a 100 ml Schlenk tube, 0.9 ml (8 mmol) of N-vinyl-5-methyloxazolidinone (R in the general formula (11)) was added. 2 A methyl compound) and 0.3 ml (4 mmol) of 2-fluoroacrylonitrile were mixed, 10.3 mg (0.06 mmol) of azobisisobutyronitrile was added, and the mixture was reacted at 60°C for 2 hours. The reaction product was added to 200 ml of methanol, reprecipitated, filtered and dried, thereby obtaining 0.7 g of the polymer of Example 6. The yield was 56%.
[0107] The polymer of Example 6 was subjected to the same treatment as that of the polymer of Example 1. 1 H-NMR determination and 19The molecular structure was determined by F-NMR measurement. The results confirmed that the polymer of Example 6 has a structural unit represented by the general formula (1) (R in the general formula (1) 1 is a hydrogen atom, R 2 is a methyl group. ) and a copolymer of a structural unit represented by formula (2).
[0108] In addition, according to Example 6 1 H-NMR spectrum and 19 The composition ratio was calculated from the integrated value of each signal in the F-NMR spectrum. As a result, the content of the structural unit represented by the formula (2) contained in the polymer of Example 6 was 74%.
[0109] "Example 7"
[0110] In a 100 ml Schlenk tube, 0.7 ml (6 mmol) of N-vinyl-5-methyloxazolidinone and 0.3 ml (4 mmol) of 2-fluoroacrylonitrile were mixed, and 8.3 mg (0.05 mmol) of azobisisobutyronitrile was added, and the mixture was reacted at 60° C. for 2 hours. The reaction product was added to 200 ml of methanol, reprecipitated, filtered and dried, thereby obtaining 0.8 g of the polymer of Example 7. The yield was 56%.
[0111] The polymer of Example 7 was subjected to the same treatment as that of the polymer of Example 1. 1 H-NMR determination and 19 The molecular structure was determined by F-NMR measurement. The results confirmed that, like the polymer of Example 6, the polymer of Example 7 has a structural unit represented by the general formula (1) (R in the general formula (1) is 1 is a hydrogen atom, R 2 is a methyl group. ) and a copolymer of a structural unit represented by formula (2).
[0112] In addition, according to Example 7 1 H-NMR spectrum and 19 The composition ratio was calculated from the integrated value of each signal in the F-NMR spectrum. As a result, the content of the structural unit represented by the formula (2) contained in the polymer of Example 7 was 65%.
[0113] "Example 8"
[0114] In a 100 ml Schlenk tube, 0.5 ml (4 mmol) of N-vinyl-5-methyloxazolidinone and 0.3 ml (4 mmol) of 2-fluoroacrylonitrile were mixed, and 6.2 mg (0.04 mmol) of azobisisobutyronitrile was added, and the mixture was reacted at 60° C. for 2 hours. The reaction product was added to 200 ml of methanol, reprecipitated, filtered and dried, thereby obtaining 0.6 g of the polymer of Example 8. The yield was 76%.
[0115] The polymer of Example 8 was subjected to the same treatment as that of the polymer of Example 1. 1 H-NMR determination and 19 F-NMR measurement to determine the molecular structure. Figure 3 Example 8 1 H-NMR measurement chart. Figure 4 Example 8 19 F-NMR measurement chart.
[0116] As a result, it was confirmed that, similar to the polymer of Example 6, the polymer of Example 8 had a structural unit represented by the general formula (1) (R 1 is a hydrogen atom, R 2 is a methyl group. ) and a copolymer of a structural unit represented by formula (2).
[0117] In addition, according to Example 8 1 H-NMR spectrum and 19 The composition ratio was calculated from the integrated value of each signal in the F-NMR spectrum. As a result, the content of the structural unit represented by the formula (2) contained in the polymer of Example 8 was 53%.
[0118] "Example 9"
[0119] In a 100 ml Schlenk tube, 0.4 ml (3 mmol) of N-vinyl-5-methyloxazolidinone and 0.3 ml (4 mmol) of 2-fluoroacrylonitrile were mixed, 5.5 mg (0.03 mmol) of azobisisobutyronitrile was added, and the mixture was reacted at 60° C. for 2 hours. The reaction product was added to 200 ml of methanol, reprecipitated, filtered and dried, thereby obtaining 0.4 g of the polymer of Example 9. The yield was 57%.
[0120] The polymer of Example 9 was subjected to the same treatment as that of the polymer of Example 1. 1 H-NMR determination and 19 The molecular structure was determined by F-NMR measurement. The results confirmed that, like the polymer of Example 6, the polymer of Example 9 has a structural unit represented by the general formula (1) (R in the general formula (1) 1 is a hydrogen atom, R 2 is a methyl group. ) and a copolymer of a structural unit represented by formula (2).
[0121] In addition, according to Example 9 1 H-NMR spectrum and 19 The composition ratio was calculated from the integrated value of each signal in the F-NMR spectrum. As a result, the content of the structural unit represented by the formula (2) contained in the polymer of Example 9 was 38%.
[0122] "Example 10"
[0123] In a 100 ml Schlenk tube, 0.5 ml (4 mmol) of N-vinyl-5-methyloxazolidinone and 0.6 ml (8 mmol) of 2-fluoroacrylonitrile were mixed, 4.4 mg (0.03 mmol) of azobisisobutyronitrile was added, and the mixture was reacted at 60° C. for 2 hours. The reaction product was added to 200 ml of methanol, reprecipitated, filtered and dried, thereby obtaining 0.6 g of the polymer of Example 10. The yield was 51%.
[0124] The polymer of Example 10 was subjected to the same treatment as that of the polymer of Example 1. 1 H-NMR determination and 19 The molecular structure was determined by F-NMR measurement. The results confirmed that, like the polymer of Example 6, the polymer of Example 10 has a structural unit represented by the general formula (1) (R in the general formula (1) is 1 is a hydrogen atom, R 2 is a methyl group. ) and a copolymer of a structural unit represented by formula (2).
[0125] In addition, according to Example 10 1 H-NMR spectrum and 19 The composition ratio was calculated from the integrated value of each signal in the F-NMR spectrum. As a result, the content of the structural unit represented by the formula (2) contained in the polymer of Example 10 was 24%.
[0126] "Comparative Example 1"
[0127] As the polymer in Comparative Example 1, polyacrylonitrile (trade name 181315, manufactured by Sigma-Aldrich Co.) was used.
[0128] "Comparative Example 2"
[0129] As the polymer of Comparative Example 2, poly(acrylonitrile-co-methyl acrylate) (trade name 517941, manufactured by Sigma-Aldrich Co., Ltd.) was used.
[0130] "Comparative Example 3"
[0131] In a 100 ml Schlenk tube, 0.4 ml (4 mmol) of N-vinyl-oxazolidinone and 1.2 ml (16 mmol) of acrylonitrile were mixed, 11.5 mg (0.07 mmol) of azobisisobutyronitrile was added, and the mixture was reacted at 60° C. for 2 hours. The reaction product was added to 200 ml of methanol, reprecipitated, filtered and dried, thereby obtaining 1.1 g of the polymer of Comparative Example 3. The yield was 78%.
[0132] The polymer of Comparative Example 3 was subjected to the same treatment as that of the polymer of Example 1. 1The molecular structure was determined by H-NMR measurement. The results confirmed that the polymer of Comparative Example 3 has a structural unit represented by the general formula (1) (R 1 and R 2 A copolymer of a structural unit derived from acrylonitrile.
[0133] In addition, according to Comparative Example 3 1 The composition ratio was calculated from the integrated value of each signal in the H-NMR spectrum. As a result, the content of the structural unit derived from acrylonitrile contained in the polymer of Comparative Example 3 was 70%.
[0134] "Comparative Example 4"
[0135] In a 100 ml Schlenk tube, 0.4 ml (4 mmol) of N-vinyl-oxazolidinone and 0.6 ml (9 mmol) of acrylonitrile were mixed, and 7.8 mg (0.05 mmol) of azobisisobutyronitrile was added, and the mixture was reacted at 60° C. for 2 hours. The reaction product was added to 200 ml of methanol, reprecipitated, filtered and dried, thereby obtaining 0.7 g of the polymer of Comparative Example 4. The yield was 70%.
[0136] The polymer of Comparative Example 4 was subjected to the same treatment as that of the polymer of Example 1. 1 The molecular structure was determined by H-NMR measurement. The results confirmed that the polymer of Comparative Example 4 has a structural unit represented by the general formula (1) (R 1 and R 2 A copolymer of a structural unit derived from acrylonitrile.
[0137] In addition, according to Comparative Example 4 1 The composition ratio was calculated from the integrated value of each signal in the H-NMR spectrum. As a result, the content of the structural unit derived from acrylonitrile contained in the polymer of Comparative Example 4 was 59%.
[0138] "Comparative Example 5"
[0139] In a 100 ml Schlenk tube, 0.4 ml (4 mmol) of N-vinyl-oxazolidinone and 0.4 ml (7 mmol) of acrylonitrile were mixed, 6.8 mg (0.04 mmol) of azobisisobutyronitrile was added, and the mixture was reacted at 60° C. for 2 hours. The reaction product was added to 200 ml of methanol, reprecipitated, filtered and dried, thereby obtaining 0.5 g of the polymer of Comparative Example 5. The yield was 68%.
[0140] The polymer of Comparative Example 5 was subjected to the same treatment as that of the polymer of Example 1. 1The molecular structure was determined by H-NMR measurement. The results confirmed that the polymer of Comparative Example 5 has a structural unit represented by the general formula (1) (R 1 and R 2 A copolymer of a structural unit derived from acrylonitrile.
[0141] In addition, according to Comparative Example 5 1 The composition ratio was calculated from the integrated value of each signal in the H-NMR spectrum. As a result, the content of the structural unit derived from acrylonitrile contained in the polymer of Comparative Example 5 was 49%.
[0142] "Comparative Example 6"
[0143] In a 100 ml Schlenk tube, 0.4 ml (4 mmol) of N-vinyl-oxazolidinone and 0.3 ml (4 mmol) of acrylonitrile were mixed, 5.9 mg (0.04 mmol) of azobisisobutyronitrile was added, and the mixture was reacted at 60° C. for 2 hours. The reaction product was added to 200 ml of methanol, reprecipitated, filtered and dried, thereby obtaining 0.6 g of the polymer of Comparative Example 6. The yield was 87%.
[0144] The polymer of Comparative Example 6 was subjected to the same treatment as that of the polymer of Example 1. 1 The molecular structure was determined by H-NMR measurement. The results confirmed that the polymer of Comparative Example 6 has a structural unit represented by the general formula (1) (R 1 and R 2 A copolymer of a structural unit derived from acrylonitrile.
[0145] In addition, according to Comparative Example 6 1 The composition ratio was calculated from the integrated value of each signal in the H-NMR spectrum. As a result, the content of the structural unit derived from acrylonitrile contained in the polymer of Comparative Example 6 was 24%.
[0146] "Comparative Example 7"
[0147] In a 100 ml Schlenk tube, 1.2 ml (12 mmol) of N-vinyl-oxazolidinone and 0.1 ml (2 mmol) of acrylonitrile were mixed, 0.9 mg (0.03 mmol) of azobisisobutyronitrile was added, and the mixture was reacted at 60° C. for 2 hours. The reaction product was added to 200 ml of methanol, reprecipitated, filtered and dried, thereby obtaining 4.5 g of the polymer of Comparative Example 7. The yield was 73%.
[0148] The polymer of Comparative Example 7 was subjected to the same treatment as that of the polymer of Example 1. 1The molecular structure was determined by H-NMR measurement. The results confirmed that the polymer of Comparative Example 7 has a structural unit represented by the general formula (1) (R 1 and R 2 A copolymer of a structural unit derived from acrylonitrile.
[0149] In addition, according to Comparative Example 7 1 The composition ratio was calculated from the integrated value of each signal in the H-NMR spectrum. As a result, the content of the structural unit derived from acrylonitrile contained in the polymer of Comparative Example 7 was 14%.
[0150] "Comparative Example 8"
[0151] In a 100 ml Schlenk tube, 0.5 ml (4 mmol) of N-vinyl-5-methyloxazolidinone (R in the general formula (11)) was added. 2 A methyl compound) and 1.0 ml (16 mmol) of acrylonitrile were mixed, 10.7 mg (0.07 mmol) of azobisisobutyronitrile was added, and the mixture was reacted at 60°C for 2 hours. The reaction product was added to 200 ml of methanol, reprecipitated, filtered and dried, thereby obtaining 0.9 g of the polymer of Comparative Example 8. The yield was 68%.
[0152] The polymer of Comparative Example 8 was subjected to the same treatment as that of the polymer of Example 1. 1 The molecular structure was determined by H-NMR measurement. The results confirmed that the polymer of Comparative Example 8 has a structural unit represented by the general formula (1) (R 1 is a hydrogen atom, R 2 A copolymer of a structural unit derived from acrylonitrile.
[0153] In addition, according to Comparative Example 8 1 The composition ratio was calculated from the integrated value of each signal in the H-NMR spectrum. As a result, the content of the structural unit derived from acrylonitrile contained in the polymer of Comparative Example 8 was 76%.
[0154] "Comparative Example 9"
[0155] In a 100 ml Schlenk tube, 0.9 ml (8 mmol) of N-vinyl-5-methyloxazolidinone and 1.0 ml (16 mmol) of acrylonitrile were mixed, 9.8 mg (0.05 mmol) of azobisisobutyronitrile was added, and the mixture was reacted at 60° C. for 2 hours. The reaction product was added to 200 ml of methanol, reprecipitated, filtered and dried, thereby obtaining 1.2 g of the polymer of Comparative Example 9. The yield was 69%.
[0156] The polymer of Comparative Example 9 was subjected to the same treatment as that of the polymer of Example 1. 1The molecular structure was determined by H-NMR measurement. The results confirmed that the polymer of Comparative Example 9 has a structural unit represented by formula (1) (R 1 is a hydrogen atom, R 2 A copolymer of a structural unit derived from acrylonitrile.
[0157] In addition, according to Comparative Example 9 1 The composition ratio was calculated from the integrated value of each signal in the H-NMR spectrum. As a result, the content of the structural unit derived from acrylonitrile contained in the polymer of Comparative Example 9 was 57%.
[0158] "Comparative Example 10"
[0159] In a 100 ml Schlenk tube, 1.4 ml (12 mmol) of N-vinyl-5-methyloxazolidinone and 1.0 ml (16 mmol) of acrylonitrile were mixed, 10.8 mg (0.07 mmol) of azobisisobutyronitrile was added, and the mixture was reacted at 60° C. for 2 hours. The reaction product was added to 200 ml of methanol, reprecipitated, filtered and dried, thereby obtaining 1.5 g of the polymer of Comparative Example 10. The yield was 67%.
[0160] The polymer of Comparative Example 10 was subjected to the same treatment as that of the polymer of Example 1. 1 The molecular structure was determined by H-NMR measurement. The results confirmed that the polymer of Comparative Example 10 has a structural unit represented by the general formula (1) (R 1 is a hydrogen atom, R 2 A copolymer of a structural unit derived from acrylonitrile.
[0161] In addition, according to Comparative Example 10 1 The composition ratio was calculated from the integrated value of each signal in the H-NMR spectrum. As a result, the content of the structural unit derived from acrylonitrile contained in the polymer of Comparative Example 10 was 44%.
[0162] "Comparative Example 11"
[0163] In a 100 ml Schlenk tube, 1.4 ml (12 mmol) of N-vinyl-5-methyloxazolidinone and 0.8 ml (12 mmol) of acrylonitrile were mixed, 9.1 mg (0.06 mmol) of azobisisobutyronitrile was added, and the mixture was reacted at 60° C. for 2 hours. The reaction product was added to 200 ml of methanol, reprecipitated, filtered and dried, thereby obtaining 1.3 g of the polymer of Comparative Example 11. The yield was 60%.
[0164] The polymer of Comparative Example 11 was subjected to the same treatment as that of the polymer of Example 1. 1The molecular structure was determined by H-NMR measurement. The results confirmed that the polymer of Comparative Example 11 had a structural unit represented by the general formula (1) (R 1 is a hydrogen atom, R 2 is a methyl group. ) and a copolymer of a structural unit derived from acrylonitrile. 1 The composition ratio was calculated from the integrated value of each signal in the H-NMR spectrum. As a result, the content of the structural unit derived from acrylonitrile contained in the polymer of Comparative Example 11 was 28%.
[0165] "Comparative Example 12"
[0166] In a 100 ml Schlenk tube, 1.4 ml (12 mmol) of N-vinyl-5-methyloxazolidinone and 0.4 ml (6 mmol) of acrylonitrile were mixed, 14.8 mg (0.09 mmol) of azobisisobutyronitrile was added, and the mixture was reacted at 60° C. for 2 hours. The reaction product was added to 200 ml of methanol, reprecipitated, filtered and dried, thereby obtaining 1.1 g of the polymer of Comparative Example 12. The yield was 60%.
[0167] The polymer of Comparative Example 12 was subjected to the same treatment as that of the polymer of Example 1. 1 The molecular structure was determined by H-NMR measurement. The results confirmed that the polymer of Comparative Example 12 has a structural unit represented by the general formula (1) (R 1 is a hydrogen atom, R 2 A copolymer of a structural unit derived from acrylonitrile.
[0168] In addition, according to Comparative Example 12 1 The composition ratio was calculated from the integrated value of each signal in the H-NMR spectrum. As a result, the content of the structural unit derived from acrylonitrile contained in the polymer of Comparative Example 12 was 13%.
[0169] "Comparative Example 13"
[0170] 0.7 ml (8 mmol) of N-vinyl-oxazolidinone and 0.6 ml (8 mmol) of 2-chloroacrylonitrile were mixed in a 100 ml Schlenk tube, 12.2 mg (0.07 mmol) of azobisisobutyronitrile was added, and the mixture was reacted at 60° C. for 2 hours. However, 2-chloroacrylonitrile was decomposed during the reaction, and no polymer was obtained.
[0171] "Comparative Example 14"
[0172] In a 100 ml Schlenk tube, 0.9 ml (8 mmol) of N-vinyl-5-methyloxazolidinone (R in the general formula (11)) was added. 2A methyl compound) and 0.6 ml (8 mmol) of 2-chloroacrylonitrile were mixed, 13.5 mg (0.08 mmol) of azobisisobutyronitrile was added, and the mixture was reacted at 60° C. for 2 hours. However, 2-chloroacrylonitrile was decomposed during polymerization, and no polymer was obtained.
[0173] In Examples 1 to 10 and Comparative Examples 3 to 14, R in the structural unit represented by the general formula (1) contained in the polymer obtained after synthesis was 2 The types of the monomers having nitrile groups used for the synthesis, and the contents of nitrile groups in the polymer obtained after the synthesis (the content of the structural unit represented by the formula (2)) are shown in Table 1.
[0174] In addition, the names of the polymer compounds of Comparative Examples 1 and 2 are shown in Table 1, respectively.
[0175] [Table 1]
[0176]
[0177] The glass transition temperature (Tg) of the polymers of Examples 1 to 10 and Comparative Examples 1 to 12 was measured by the following method.
[0178] (Measurement method of glass transition temperature (Tg))
[0179] Using a high-sensitivity differential scanning calorimeter (trade name, DSC6200, manufactured by Seiko Instruments Inc.), in a nitrogen atmosphere, the temperature was raised from 30°C to 200°C at a heating rate of 20°C per minute, the temperature was lowered from 200°C to 30°C at a cooling rate of 40°C per minute, and the temperature was raised from 30°C to 200°C at a heating rate of 20°C per minute. The inflection point during the second heating was determined as the glass transition temperature (Tg).
[0180] In addition, using the polymers of Examples 1 to 10 and Comparative Examples 1 to 12 as piezoelectric materials, piezoelectric films were produced by the following method, and the piezoelectric constant d33 was measured. The results are shown in Table 1.
[0181] (Manufacturing of piezoelectric film)
[0182] The piezoelectric material was dissolved in N,N-dimethylformamide as a solvent to prepare a 20 mass % polymer solution (coating solution). The obtained polymer solution was coated on a PET film (trade name, Lumirror (registered trademark), manufactured by Toray Industries, Ltd.) as a substrate in a manner to achieve a thickness of 50 μm after drying to form a coating film. Then, the coating film formed on the PET film was dried on a hot plate at 120° C. for 6 hours to remove the solvent in the coating film, thereby obtaining a piezoelectric material sheet.
[0183] The obtained piezoelectric material sheet was peeled off from the PET film, and electrodes made of aluminum were respectively provided on one surface and the other surface of the piezoelectric material sheet by evaporation. Then, a high-voltage power supply device HARB-20R60 (manufactured by Matsusada Precision Inc.) was electrically connected to the electrodes of the piezoelectric material sheet, and maintained at 140°C for 15 minutes while applying an electric field of 100 MV / m. Then, the piezoelectric material sheet was slowly cooled to room temperature while applying a voltage, and a polarization process was applied to obtain a sheet-like piezoelectric film.
[0184] (Measurement method of piezoelectric constant d33)
[0185] The piezoelectric film was mounted on a measuring device using a pin with a tip diameter of 1.5 mm as a sample fixing jig. As a measuring device for the piezoelectric constant d33, a PiezoMeter System PM200 from PIEZOTEST was used.
[0186] The measured value of the piezoelectric constant d33 is positive or negative depending on the front and back surfaces of the piezoelectric film being measured. In this specification, the absolute value of the measured value is described as the value of the piezoelectric constant d33.
[0187] As shown in Table 1, it can be confirmed that the polymers of Examples 1 to 10 have higher glass transition temperatures (Tg) than the polymers of Comparative Examples 1 and 2, and have better heat resistance.
[0188] In addition, the polymers of Examples 1 to 10 all had sufficiently high glass transition temperatures (Tg) and were excellent in heat resistance.
[0189] As shown in Table 1, the piezoelectric films of Examples 1 to 10 containing the polymers of Examples 1 to 10 have higher piezoelectric constants d33 and better piezoelectric characteristics than the piezoelectric film of Comparison Example 1 containing the polymer of Comparison Example 1 and the piezoelectric film of Comparison Example 2 containing the polymer of Comparison Example 2.
[0190] In addition, the piezoelectric films including the polymers of Examples 1 to 10 all had higher piezoelectric constants d33 than the piezoelectric films including the polymers of Comparative Examples 3 to 12, and had better piezoelectric characteristics.
[0191] In particular, the piezoelectric films of Examples 3 to 5, Examples 8 and 9, which contain 30 to 60 mol % of the polymer containing the structural unit represented by formula (2), and R containing the structural unit represented by formula (1) 2 Compared with a piezoelectric film of a polymer having the same structure and a content of the structural unit represented by formula (2) of less than 30 mol % or more than 60 mol %, the piezoelectric constant d33 is higher and the piezoelectric characteristics are better.
[0192] Industrial Applicability
[0193] A piezoelectric material capable of obtaining a piezoelectric film having high heat resistance and piezoelectric characteristics can be provided.
[0194] A piezoelectric film having high heat resistance and piezoelectric characteristics can be provided.
[0195] A piezoelectric element including a piezoelectric film having excellent heat resistance and piezoelectric characteristics can be provided.
Claims
1. A copolymer, wherein It has a structural unit represented by the following general formula (1) and a structural unit represented by the following formula (2), In the general formula (1), R 1 is any one selected from the group consisting of a hydrogen atom, a methyl group, a dimethyl group, an ethyl group, an isopropyl group, an isobutyl group, a phenyl group, and a benzyl group, and R 2 is a hydrogen atom or a methyl group, or R 1 and R 2 Together with the oxazolidinone ring, it forms a benzoxazolidinone skeleton.
2. The copolymer according to claim 1, wherein In the general formula (1), R 1 is a hydrogen atom, R 2 A hydrogen atom or a methyl group.
3. The copolymer according to claim 1 or 2, wherein The content of the structural unit represented by the formula (2) is 10 to 80 mol%.
4. A piezoelectric material, wherein: The copolymer comprising claim 1 or 2.
5. A piezoelectric film, wherein: The copolymer comprising claim 1 or 2.
6. A piezoelectric element, wherein: A piezoelectric film according to claim 5, and electrodes respectively arranged on one surface and the other surface of the piezoelectric film.
Citation Information
Patent Citations
Control device and method, as well as solid state image sensor and method
JP2022115444A
Vinylidene cyanide alternating copolymers
WO1991013922A1